Estudo farmacognóstico e avaliação das atividades Anti-inflamatória e analgésica das folhas do nabo forrageiro (Raphanus sativus L. var. oleifera Metzg.) - Paula, Bruno Faria De (2014)
Medicinal plants are commonly used by the population to replace or assist the healing process. Within this surrounding context, the wild radish, Raphanus sativus L. var. oleiferus Metzg., wich belongs to the Brassicaceae family, also known as crucifera, is a plant with known classes of bioactive compounds, as well as the Raphanus sativus L itself. In this work, studies were conducted to obtain physico-chemical parameters of the drug as grain size, total and acid insoluble ashes, loss on drying and extractive substances, and studies to the knowledge of its bioactive and phytochemical potential, with tests such as analgesia and inflammation and phytochemical screening complemented with mass spectrometry of dry extract. The physico-chemical parameters classified the drug as moderately coarse size particles, and values​ ​of total and acid insoluble ashes of 16.69 and 0.025% respectively. The loss on drying was 6.96% and extractive substances representing 25% of the total mass of drug. Phytochemical screening revealed the presence of important pharmacognostic classes such as flavonoids, steroids, triterpenes and tannins, which could be extensively associated with biological activity. In addition, chemical structures were proposed for the flavonoids and other compounds found in dry extract of R. sativus, as the kaempferol and quercetin as the flavonoids and glicorrafenine as a glucosinate. The biological tests showed: absence of acute toxicity at the tested concentrations; an anti-inflammatory activity comparable to indomethacin in the standard concentrations of 30, 100 and 300 mg/kg of dry extract peritonitis test. You paw edema test, the most active and comparable to the standard activity concentrations were 30 and 300 mg/kg. The analgesia test made ​​by the methodology of formalin better activity of the extract at the concentration of 300 mg/kg whereas the activity of the other two concentrations (30 and 100 mg/kg) showed no significant effect. The hot plate test, however, showed no antinociceptive favorable result of dry extract.